Crust and upper mantle shear velocity structure beneath the Tibetan plateau and surrounding regions from interevent surface wave phase velocity inversion - Curtis, A; Woodhouse, J (1997)
Average a priori shear velocity models are constructed for the Tien Shan, Tarim basin, Pamir-Hindu Kush, Himalaya and NE India. These models are shown to account for most of the lateral velocity heterogeneity at wavelengths > 1000 km. Interevent fundamental mode Rayleigh and Love wave phase velocities were measured in the period range 32-200 s and were inverted for path-averaged shear velocity structures. These, in turn, were regionalized to estimate average, isotropic structures beneath the six regions listed above. Low upper mantle velocities are observed beneath the western and eastern Tien Shan. The Tarim basin structure is poorly constrained but exhibits very low upper crustal velocities (probably due to deep sedimentary accumulation), and either very high upper mantle velocities exist (> 4.8 km/s) in a layer 70 km thick or the lithosphere is very thick (∼180 km). Low upper mantle velocities are observed beneath the Chang Thang region, the central, and the northeast plateau but not beneath the southern or southeastern plateau. The crustal velocity gradient with depth is zero in the east central plateau consistent with lower crustal basaltic intrusions there but is positive to the west and southeast of this zone. Upper mantle structures show that the Indian lithosphere could have subducted beneath the entire plateau only if either 1 mantle in the depth range 115-185 km has been altered (or removed) to reduce its average velocity or 2 the Indian lithosphere is only ∼85 km thick.